Granular dampers: does particle shape matter? - Hamzeh Pourtavakoli; Eric J R Parteli; Thorsten Pöschel (New Journal of Physics, 2016)
By means of particle-based numerical simulations using the discrete element method, we address the question of how the performance of granular dampers is affected by the shape of the granular particles. In consistence with previous experiments performed with nearly spherical particles we find that independently of the particles’ shape, the granular system is characterized by a gas-like regime for small amplitudes of the container’s oscillation and by a collect-and-collide regime for large amplitude forcing. Both regimes are separated by an optimal operation mode—the critical amplitude of the damping oscillation for which the energy dissipation is maximal—which is independent of the particle shape for given conditions of particle mass, material properties and number of particles. However, in the gas-like regime, we find that spherical particles lead to more efficient energy dissipation compared to complex shaped particles of the same mass. In this regime, a dependence on the damper’s efficiency on the particle shape is found.